2019
DOI: 10.5089/9781498317047.001
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Investment Since the Tax Cuts and Jobs Act of 2017

Abstract: There is no consensus on how strongly the Tax Cuts and Jobs Act (TCJA) has stimulated U.S. private fixed investment. Some argue that the business tax provisions spurred investment by cutting the cost of capital. Others see the TCJA primarily as a windfall for shareholders. We find that U.S. business investment since 2017 has grown strongly compared to pre-TCJA forecasts and that the overriding factor driving it has been the strength of expected aggregate demand. Investment has, so far, fallen short of predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 15 publications
(20 reference statements)
3
25
0
Order By: Relevance
“… See, for example, Basu, ; Kopp, Leigh, Mursula, & Tambunlertchai, . This value of σ = 2.66 implies a markup of around 60%, which is consistent with recent evidence from Kopp et al.…”
supporting
confidence: 85%
“… See, for example, Basu, ; Kopp, Leigh, Mursula, & Tambunlertchai, . This value of σ = 2.66 implies a markup of around 60%, which is consistent with recent evidence from Kopp et al.…”
supporting
confidence: 85%
“…This article is also related to the literature on how policy uncertainty and market concentration influence the investment responses to taxes. Recent literature has shown that increased economic policy uncertainty and greater corporate market power have played a role in subduing private investment (see, for example, Baker et al, 2016;Kopp et al, 2019). I conduct heterogeneity analyses that examine the impacts of policy uncertainty and competition on firms' response.…”
Section: Introductionmentioning
confidence: 99%
“…If we next define as the investment-GDP ratio, then it follows that A higher investment-to-GDP ratio leads to faster capital stock growth -at constant capacity utilization. Since empirically investment is usually completely dominated by 'accelerator effects' operating through aggregate demand (Kopp et al 2019), it follows from (14) and (15) that a structural decline in demand growth depresses TFP growth -through stagnating business investment, a decline in capital deepening and/or declining capacity utilization. As a result, the growth rate of potential output must be low -this causal chain is illustrated in Figure 2.…”
Section: Bringing Demand In From the Coldmentioning
confidence: 99%